Conceptualizing Political Consumerism: How Citizenship Norms Differentiate Boycotting from Buycotting. (13th September 2013) - Copeland, Lauren
Abstract : Most of the literature treats boycotting and buycotting – which collectively comprise political consumerism – as homogeneous acts, reflecting a single mode of behavior. However, several key differences between boycotts and buycotts suggest that the predictors of boycotting should be somewhat different from those of buycotting. In this article, I theorize that boycotting is more strongly associated with dutiful citizenship norms because it is punishment oriented and has several key features in common with electoral, interest‐based politics. Buycotting, conversely, is more strongly associated with engaged citizenship norms because it is reward oriented and has more features in common with civic engagement. To test these theoretical expectations, I use original, nationally representative US survey data. The findings confirm my theoretical expectations, and they point to the role of changing citizenship norms rather than more traditional factors such as resources and psychological engagement as important in understanding contemporary political participation.